Analysis of Marketing Strategies in Increasing Sales of Pesticide Products - Helda Megania Telaumbanua; Yupiter Mendrofa; Idarni Harefa Harefa; Emanuel Zebua Zebua (Golden Ratio of Data in Summary, 2024)
Agriculture is a very important sector in Indonesia, because it has natural resources (SDA) and Human Resources (HR). Based on researchers' observations that have been carried out at UD. Makmur Tani uncovered problems involving many similar, tight competing companies with limited pesticide products and inappropriate marketing strategies. This research aims to analyze the marketing strategy implemented by UD. Makmur Tani in an effort to increase sales of pesticide products. The main focus of the research is on the three main indicators of marketing strategy, namely segmentation, targeting and positioning. Based on this explanation, the type of research used in this research is qualitative research, which is because it is not in the form of numbers or numbers so it only takes the form of statements or sentences. The research results show that UD. Makmur Tani has implemented a market segmentation strategy based on geography and farmer demographics. In terms of targeting, the company focuses on farmers in certain regions. The positioning strategy implemented is by positioning certain products. Further analysis revealed that implementation of this strategy has contributed to increased sales of pesticide products. However, there are still several obstacles in its implementation, especially related to market competition and changes in consumer preferences.